Pengaruh Konfigurasi Shearwall Terhadap Kapasitas Struktur Gedung Bertingkat - Agustinus Sungsang Nana Patria; Haq, Ya’la Amirul (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
Multi-storey buildings are very vulnerable to lateral forces arising from earthquakes. Therefore, in the construction of high-rise buildings, it is necessary to use lateral force resisting elements, one of which is the use of shearwall. This research was conducted to analyze the comparison of the use of shearwall configurations with 3 different configuration models to see the best structural behavior and building strength. and 1 model without shearwall for comparison. All materials and dimensions used are the same. Analysis was carried out using SNI-1726:2019 and SNI-2847:2019 with modeling in the ETABS V.17.0.1 program to obtain basic shear forces, structural behavior and deviations between levels. The results show that based on three models of shearwall configuration variations, the largest earthquake direction x base shear value is found in the existing model, followed by variation 1 and the smallest is found in variation model 2. The structural behavior of the three well-behaved models is shown by dominant translation in the x and y directions. The highest inter-level deviation value is in the existing model but does not meet SNI requirements. From the results of the analysis, the variations created tend to be better than the existing model.